The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2018)
The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 is erected. Seventeen species of the group from the East Asia, including G. smetanai sp. n. (Sichuan, China), are reviewed and keyed. Geodromicus iburinus (Watanabe, 1990) and G. nipponensis (Watanabe, 1990) are revalidated; G. hermani (Watanabe, 1991) syn.n. is synonymized with G. nipponensis (Watanabe, 1990); G. kirschenblati Tichomirova, 1973 is resynonymized with G. sibiricus Bernhauer, 1915; lectotypes for G. chinensis Bernhauer, 1938 and G. lestevoides (Sharp, 1889) are designated. The distributional maps for eight species are provided; the genital structures of fourteen species are figured.